If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 6 = -24 + -1t Reorder the terms: 6 + 5t = -24 + -1t Solving 6 + 5t = -24 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. 6 + 5t + t = -24 + -1t + t Combine like terms: 5t + t = 6t 6 + 6t = -24 + -1t + t Combine like terms: -1t + t = 0 6 + 6t = -24 + 0 6 + 6t = -24 Add '-6' to each side of the equation. 6 + -6 + 6t = -24 + -6 Combine like terms: 6 + -6 = 0 0 + 6t = -24 + -6 6t = -24 + -6 Combine like terms: -24 + -6 = -30 6t = -30 Divide each side by '6'. t = -5 Simplifying t = -5
| 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 | | 36x=-8x | | 25b^4-211b^2+3024=0 | | 3(n-2)=3(2n+4) | | -10+2j=-2 | | 6x(4+3)= | | X^72/8x^4 | | -5(x-1)=-10x+20 | | B^0/ba^5 | | (9)(10)-(3)(4)= | | 3w+6+4w= | | 5x+6y=67 | | 7x(1/3xN)-4=10 | | 6x-3=14x-19 | | 4(z-3)=5-3z | | (7(1/3y))-4=10 | | (M)(10)=n | | 5x-10(x-2)=x^2 | | 3ab^2-6b= | | 15x=7x-(11-4x) | | 0.75x=24 | | X^72/8x4 | | 2p/3p | | 8.1a+2.3=5.1-3.1 | | 5b-5=7b |